Alkali-Soluble Pectin Is the Primary Target of Aluminum Immobilization in Root Border Cells of Pea (Pisum sativum) - Yang, Jin; Qu, Mei; Fang, Jing; Shen, Ren Fang; Feng, Ying Ming; Liu, Jia You; Bian, Jian Feng; Wu, Li Shu; He, Yong Ming; Yu, Min (Frontiers in Plant Science, 2016)
We investigated the hypothesis that a discrepancy of Al binding in cell wall constituents determines Al mobility in root border cells (RBCs) of pea (Pisum sativum), which provides protection for RBCs and root apices under Al toxicity. Plants of pea (Pisum sativum L. ‘Zhongwan no. 6’) were subjected to Al treatments under mist culture. The concentration of Al in RBCs was much higher than that in the root apex. The Al content in RBCs surrounding one root apex (104 RBCs) was approximately 24.5 % of the total Al in the root apex (0–2.5 mm), indicating a shielding role of RBCs for the root apex under Al toxicity. Cell wall analysis showed that Al accumulated predominantly in alkali-soluble pectin (pectin 2) of RBCs. This could be attributed to a significant increase of uronic acids under Al toxicity, higher capacity of Al adsorption in alkali-soluble pectin (5.3-fold higher than that of chelate-soluble pectin), and lower ratio of Al desorption from alkali-soluble pectin (8.5%) compared with chelate-soluble pectin (68.5%). These results indicate that alkali-soluble pectin is the primary target of Al immobilization in RBCs of pea, which impairs Al access to the intracellular space of RBCs and mobility to root apices, and therefore protects root apices and RBCs from Al toxicity.